Fatigue crack growth in welded S355 specimens subjected to combined loadings (Fracture and Structural Integrity, 2019)
The paper presents a result of experimental tests of welded S355 specimens subjected to combined bending and torsion loading. In order to analyse how the fillet joints’ shape and the load ratio affect the crack growth, we selected two kinds of the fillet shape: concave and convex, and two load ratios, namely R = -1, 0. Rectangular specimens with stress concentrators in form of the external two-sided blunt notches and fillet welded joint were tested. The test results were compared to experiments conducted on solid specimens without welds.
Keywords: Welding; Bending and torsion; Fatigue crack growth; Microhardness